Synthesis, spectral and thermal studies on dicarboxylate-bridged palladium(II) coordination polymers. Part II - Fernandes, R. L. [UNESP]; Takahashi, P. M. [UNESP]; Frem, R. C. G. [UNESP]; Netto, A. V. G. [UNESP]; Mauro, A. E.; Matos, J. R. (Springer, 2009)
The synthesis and thermal behavior of the new [Pd(fum)(bipy)] (n) center dot 2nH(2)O (1), [Pd(fum)(bpe)] (n) center dot nH(2)O (2) and [Pd(fum)(pz)] (n) center dot 3nH(2)O (3) {bipy = 4,4'-bipyridine, bpe = 1,2-bis(4-pyridyl)ethene and pz = pyrazine} fumarate complexes are described in this work as well their characterization by IR and (13)C CPMAS NMR spectroscopies. TG curves showed that the compounds released organic ligands and lattice water molecules in the temperature range of 46-491 A degrees C. In all the cases, metallic palladium was identified as the final residue.
Keywords: Palladium(II); Fumarate; N-based linear spacers; Thermal studies; Coordination polymers